Financial Well-being Model of Health Workers in the City of Surabaya: An Empirical Study - Soepardi, Gerryd Dina; Iramani, Rr. (Dinasti Publisher, 2025)
This research examines the influence of financial knowledge, current financial stress, and internal locus of control on the financial well-being of civil servant healthcare workers in Surabaya. The study is motivated by the growing importance of understanding the factors that shape financial well-being, particularly among public sector workers who play a vital role in delivering health services. Samples were taken using cluster sampling techniques at health centers in the Surabaya area. Data was collected using a survey method by distributing questionnaires to selected respondents totaling 150 respondents. This research uses a quantitative approach where the analysis technique used is Structural Equation Model-Partial Least Square (SEM-PLS). The results indicate that financial knowledge does not have a significant effect on financial well-being. Financial stress has a significant negative effect while internal locus of control has a significant positive effect. The implications of the results of this study emphasize the importance of strengthening the psychological to manage their finances independently and sustainably in order to achieve financial well-being.